Cropland Exposed to Drought Is Overestimated without Considering the CO2 Effect in the Arid Climatic Region of China - Shan Jiang; Jian Zhou; Guojie Wang; Qigen Lin; Ziyan Chen; Yanjun Wang; Buda Su (Land, 2022)
Drought seriously restricts people’s lives and social–economic development. An accurate understanding of the evolution of drought characteristics and future changes in cultivated land exposure can reduce the risk of drought. There is evidence that increased CO2 concentrations alter the physiological properties of vegetation and, thus, affect drought evolution. In this study, both changes and differences in drought (i.e., characteristics and cropland exposure) with and without the CO2 effect over the arid region of China are investigated, using seven CMIP6 outputs and land-use under seven shared-socioeconomic-pathway (SSP)-based scenarios. The results show that: (1) drier conditions will be more severe in 2015–2100 under SSP5-8.5, especially if the CO2 effect is neglected. Moreover, the CO2 effect will increase with increasing emission concentrations; (2) drought intensity will be greater than in the baseline period (1995–2014, approximately −1.45) but weaker than that without the CO2 effect under all scenarios; (3) drought frequency will decrease, and will generally decline faster if the CO2 effect is not considered; (4) drought duration will increase and the difference between the presence and absence of the CO2 effect will always be smallest under SSP1-1.9 and largest under SSP5-8.5; (5) drought acreage will also increase, and neglecting the CO2 effect is always higher than that considering CO2. The difference between the two algorithms will increase with time; and (6) cropland exposure to drought will increase, and can even reach 669,000 km2 and 524,000 km2 considering and ignoring the CO2 effect, respectively. Our findings suggest that ignoring CO2 in drought evaluations will result in significant overestimations of drought projections.